Perbandingan Persentase Perekat Arpus 17,5% dan 20% terhadap Kualitas Briket Cangkang Kelapa Sawit - Azhar Basyir Rantawi; Ahdiat Leksi Siregar; Alif Rizkullah (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
The carbon content of oil palm shells has the potential to be used as an energy source, namely as fuel briquettes. This study discusses the effect of using arpus adhesive with a composition of 17.5% and 20% on the quality of briquettes. Parameters observed were moisture content, burning time, calorific value when wet and dry, ash content when wet and dry, carbon content when wet and dry, and volatile matter content when wet and dry. The results showed that the use of arpus adhesive with a composition of 17.5% and 20% affected the quality of briquettes from oil palm shells. The best composition is 17.5% which shows better results on all briquette quality parameters.